Converging Realities & Flexible Memory Rebuilding upon Socio-tech Shifts: Reflecting on Hippocampal Limbus (Global Journal of Human-Social Science, 2024)
In our evolving era, memory, technology, and society intersect, prompting a reevaluation of human experience. Adaptive recall systems help navigate the blurred lines between personal and collective realities. This text tackles aging and brain herpes as experience highlighters, emphasizing the need for adaptive strategies and memory-enhancing techniques. Memory relies on automatic processes, with the hippocampus key for episodic reconstructions. Technology enhances cognitive abilities, merging individual and collective understandings, and redefining truth and reality while fostering resilience and adaptability. This study embraces diverse perspectives to enrich our understanding, inviting interconnectedness, creativity, compassion, and new forms of humanism.
Keywords: memory; technology; adaptation; cognitive flexibility; stress; shared experiences; contextual recall; neuroplasticity